Wokół estetyki filmowej kulturotwórczych żywiołów. Analiza wybranych kadrów z filmu „Romeo i Julia" Baza Luhrmanna - Stachowiak-Dudzik, Elżbieta (Załącznik Kulturoznawczy, 2024)
This text presents an analysis of selected frames from Baz Luhrmann’s 1996 film Romeo+Juliet. The author examines the aesthetics of material elements – fire and water – drawing on Gaston Bachelard’s concept of imagination, supplemented by Maurice Merleau-Ponty’s phenomenological theory of perception and Jung’s idea of archetypes. Through the lens of specific hermeneutics of faith (aiming to restore meaning to a text) and a foundational understanding of primordial symbols, she explores their cinematic manifestations. The researcher incorporates traditions of phenomenology and hermeneutics not only by referencing particular theories, but also by employing an essayistic style of argumentation, rich with metaphors and intertextual (or even inter-visual) references. This literary and scientific description is further enriched with comparative elements. Through a reference to William Shakespeare’s original drama, the author seeks to capture the interplay of meanings that emerge from intersemiotic translation, particularly in the relationship between word and image. The analyzed film frames serve as a starting point to ponder the essence of symbolization and the symbol itself, understood as the unity of opposites. The primary aim of this creative analysis is to invite the reader to engage in a game of associations and to participate in culture-creating symbolic interpretations.